2022
DOI: 10.3389/fneur.2022.778419
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis in Alzheimer's Disease Is Associated With Increased Excitatory Neuron Vulnerability and Post-transcriptional Mechanisms Altering Synaptic Protein Levels

Abstract: Alzheimer's disease with psychosis (AD+P) is a heritable phenotypic variant of the disease which is associated with more rapid cognitive deterioration compared to Alzheimer's disease without psychosis (AD–P). Cognitive decline in AD correlates with synapse loss, and our previous studies suggest that those with AD+P have a differentially affected synaptic proteome relative to those with AD–P. In this study, we utilized RNA-sequencing of dorsolateral prefrontal cortex (DLPFC) in a cohort of 80 AD cases to evalua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…There was a signi cant shift of almost all proteins to lower levels in AD+P in comparison to AD-P (t = -90.6, df=1612, p<2x10 -307 ). Additional analyses con rmed the robustness of this downregulation: analysis of the larger set of proteins resulting when using peptides quanti ed in at least 50% of samples; analysis of the 51 individuals included in our prior report of a targeted panel of 190 synaptic proteins [16], or the remaining 55 AD subjects who were newly evaluated; and; analysis covarying for excitatory neuron proportion which we previously reported is reduced in AD+P relative to AD-P [17] (Figure S4A-F).…”
Section: Psd Protein Levels In Ad With and Without Psychosismentioning
confidence: 61%
See 1 more Smart Citation
“…There was a signi cant shift of almost all proteins to lower levels in AD+P in comparison to AD-P (t = -90.6, df=1612, p<2x10 -307 ). Additional analyses con rmed the robustness of this downregulation: analysis of the larger set of proteins resulting when using peptides quanti ed in at least 50% of samples; analysis of the 51 individuals included in our prior report of a targeted panel of 190 synaptic proteins [16], or the remaining 55 AD subjects who were newly evaluated; and; analysis covarying for excitatory neuron proportion which we previously reported is reduced in AD+P relative to AD-P [17] (Figure S4A-F).…”
Section: Psd Protein Levels In Ad With and Without Psychosismentioning
confidence: 61%
“…Most recently, we examined gray matter levels of a limited panel of 190 synaptic proteins in individuals with AD+P and found reductions in canonical postsynaptic density (PSD) proteins relative to AD-P subjects [16]. These differences exceeded those which could be accounted for by any differences in neuropathology burden between the groups [16], or by reduction in the corresponding mRNA transcripts due to greater excitatory neuron loss in AD+P [17].…”
Section: Introductionmentioning
confidence: 99%
“…The data presented here represents the first exploration of affective, apathy, and agitation symptoms on the transcriptome-wide level and establishes unique patterns of mRNA expression in one of the most consistently implicated brain regions to BPSD, the ACC [49][50][51]. In addition, we add to the growing knowledge base about transcriptional changes in AD with psychosis [28] (discussed in greater detail along with the affective and apathy domain in supplementary materials). We confirmed that commonly co-occurring BPSD symptoms cluster into domains in our cohort and that these domains are typified by unique transcriptional signatures in the ACC, even when individual samples are used in an overlapping design.…”
Section: Discussionmentioning
confidence: 71%
“…The main novelty of our study is that it is the first, to our knowledge, to study the affective, apathy, and agitation domains on the transcriptome-wide level, which is comparable to the many studies of cognition in AD [73,75,77], dating back at least as early as 2008 [72], and the recent study of AD with psychosis [28].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation